Mystery at the Washington Monument - Roy, Ron, 1940-; Bush, Timothy (New York : Random House, 2007)
When KC and Marshall see lights flickering at night in the Washington Monument, their investigation turns up a monkey, a hole in one of the monument stones, and a hundred-year- old mystery.
"A Stepping Stone book."
Keywords: Monkeys -- Juvenile fiction; Theft -- Juvenile fiction; Washington (D.C.) -- Juvenile fiction; Mystery fiction